Performance Comparative Analysis of Monocrystalline and Polycrystalline Single Diode Solar Panel Models using the Five Parameters Method - Rahman, Rizal Akbarudin; Aripriharta, Aripriharta; Putranto, Hari (Frontier Energy System and Power Engineering, 2019)
The use of renewable energy as a source of electrical energyincreases every year. Unfortunately, Indonesia does not have manypower plants that utilize renewable energy sources. The mostpotential renewable energy in Indonesia is the sunlight with the helpof solar panels that converts solar energy into electrical energy.However, the environment could affect the solar panel module andin turn, affect the performance of solar panels or the generatedelectric energy. This research calculated the performance of solarpanels with a single-diode model using the Five Parameters methodthat required solar panel module specification data, the totalradiation absorbed by the solar panel module, and the temperatureof the environment. The Five Parameters method is a methodmodeled after solar panel module performance in the form of thesingle-diode equivalent circuit. The Five Parameters method isreliable in predicting the energy produced by the solar panels whenthe input data is limited. The results for using the Five Parametersin monocrystalline solar panels were Isc = 1.827 A, Imp = 0.662 A,Voc = 18.221 V, Vmp = 15.019 V, Pmp = 9.955 W. And the results inpolycrystalline solar panels were Isc = 1.926 A, Imp = 0.686 A, Voc =17.594 V, Vmp = 14.166 V, Pmp = 9.722 W. Based on the results; itwas concluded that the most efficient and optimised types of solarpanels on natural conditions in Sendang Biru Beach was themonocrystalline solar panel because it produced electrical outputpower of 9.955 W. Therefore, there could be a manufacturer ofsolar energy power plants to reduce the cost of electricity in thecoastal area, such as in Sendang Biru Beach.